Using participatory research to expand the customer base of farmers markets - Gail Feenstra; Julia Van Soelen Kim; Penny Leff; Suzanne Grady; Summer Sullivan; Susan Garcia (Urban Food Systems Symposium, 2020)
Direct-to-consumer sales (DTC) through farmers markets, CSAs, and urban farm stands is an important venue for bringing fresh, nutritious, and regional food to urban consumers and creating economic and social linkages between urban and peri-urban farms. However, many urban consumers who use government food programs have limited access to DTC markets. Farmers Market LIFE (Local Incentives for Food and Economy) seeks to expand the customer base of farmers market shoppers in Sonoma County, California, through the acceptance of SNAP (the Supplemental Nutrition Assistance Program) and Market Match, a dollar-for-dollar nutrition incentive program that makes farmers markets more economically accessible to low-income shoppers while also increasing overall sales for farmers’ market vendors. We explore the use of “environmental scans” an innovative research instrument used at farmers’ markets to identify social, cultural, linguistic, behavioral and economic obstacles and opportunities for low-income consumers and people of color to shop at farmers’ markets. Community partners co-designed and gathered data about selected farmers markets using environmental scans in fall 2019. This methodology has proved effective in providing insight into farmers’ market dynamics including potential barriers and solutions to make farmers’ markets more accessible and inviting to SNAP customers and people of color. We share results of this tool as a method that others interested in community-engaged research may want to use to investigate their own unique farmers’ market settings and to illustrate the nature of findings from our application of the tool in Sonoma County, California, in 2019.
Keywords: food systems research; community-engaged research; SNAP; nutrition incentives; low-income farmers market shoppers; environmental scan